Ebola Lessons for a Global Village: I am my brothers' (and sisters') keeper - Frank Thomas Houghton; Sharon Houghton (Social Medicine Publication Group, 2020)
The ongoing Ebola outbreak is estimated to have resulted in over 8,300 deaths, and is the largest such outbreak in recorded history. Although largely confined, this time, to West Africa the ramifications of the disease have been global. Widespread transmission of the disease was evident in Guinea, Liberia, Sierra Leone, with additional cases also noted in Mali, Nigeria, Senegal, Spain, the UK and the USA.